Blended Islamic philanthropy model of green sukuk and digital waqf: Maqasid al-Shariah approach to sustainable economic development in Indonesia - Octaviano, Dicky; Brennaf, Muhammad Senoyodha; Rahmi, Arifah (Indonesian Journal of Islamic Economics Research, 2026)
Indonesia’s agriculture and fisheries sectors face an annual financing gap that existing conventional banking and Islamic financial instruments, which operate separately, have failed to address. Three unresolved gaps motivate this study: empirically, no prior study has measured the combined mobilization potential of Indonesia’s cumulative green sukuk program and digital waqf against this structural financing deficit; theoretically, no integrated governance framework grounded in Maqasid al-Shariah has been proposed to connect philanthropic waqf capital with commercial sukuk financing in a single blended architecture; and at the policy level, the regulatory divide between OJK and BWI lacks a unified instrument design. This paper proposes the Maqasid-Based Blended Islamic Philanthropy (MBIP) Model, a novel three-layer architecture integrating digital waqf as a first-loss philanthropic foundation, green sukuk as the commercial-concessional superstructure, and a blockchain-enabled Digital Governance Architecture as the integrating keystone. Employing a PRISMA-guided systematic literature review and secondary data analysis from OJK, BWI, BPS, and DJPPR, the model operationalizes all five Maqasid al-Shariah objectives with proposed measurable indicators (waqf mobilization rate, sukuk yield spreads, SDG alignment scores) and aligns with key SDGs. The study contributes four testable propositions and actionable policy recommendations for OJK, BWI, and DSN-MUI.